CVD-grown copper tungstate thin films for solar water splitting. Issue 22 (21st March 2018) - Peeters, D.; Mendoza Reyes, O.; Mai, L.; Sadlo, A.; Cwik, S.; Rogalla, D.; Becker, H.-W.; Schütz, H. M.; Hirst, J.; Müller, S.; Friedrich, D.; Mitoraj, D.; et al.
Abstract : In this paper, a direct chemical vapor deposition (CVD) approach is applied for the first time to synthesize high quality copper oxide (CuO), copper tungstate (CuWO4 ) and tungsten oxide (WO3 ) on F:SnO2 (FTO) substrates for photocatalytic water splitting. Abstract : In this paper, a direct chemical vapor deposition (CVD) approach is applied for the first time to synthesize high quality copper oxide (CuO), copper tungstate (CuWO4 ) and tungsten oxide (WO3 ) on F:SnO2 (FTO) substrates for photocatalytic water splitting. Variation of process parameters enables us to tune the stoichiometry of the deposits to obtain stoichiometric, W-rich, and Cu-rich deposits. It is found that the presence of Cu in WO3 thin films reduces the bandgap and enhances the absorption properties of the material in the visible range. The photoelectrocatalytic performance of stoichiometric CuWO4 was found to be superior to that of WO3 oxide under frontside illumination when thin films were used. However, detailed photoelectrochemical investigations of both thin and thicker CuWO4 films reveal that the incorporation of copper also decreases the mobility of both electrons and holes, the latter being the performance-limiting factor. These results are in line with our first-principles calculations of the electronic structure of CuWO4 . A charge carrier mobility and diffusion length of ∼6× 10 −3 cm 2 V −1 s −1 and 30 nm were determined by time-resolved microwave conductivity measurements, values comparable to those of undoped bismuth vanadate (BiVO4 ). Our findings establish new insights into the advantages and limits of CuWO4 -based photoanodes, and suggest a possibility of using very thin CuWO4 films on top of highly absorbing semiconductors with optimal electronic properties.